Analysis of Factors Influencing Students’ Willingness to Speak English in English Classroom Interaction - Adinda Puteri Zulaika; Ririn Ovilia (Universitas Negeri Padang, 2022)
The practical elements determining success in learning a foreign language are willingness to communicate (WTC) factors (McIntyre, Clement, Dornyei, and Noels, 1998). This research aimed to determine students' willingness to speak English in classroom interaction. This study utilized questionnaires and interviews conducted using the Focus Group Discussion (FGD) method, with an explanatory research design. The information was gathered through the distribution of a questionnaire and interviews. The population of this study was the tenth student class of SMAN 10 Padang. 6 students were interviewed through focus group discussions, and 72 students used the questionnaire. Furthermore, the researcher summarized the interview results and used descriptive statistics to analyze the questionnaire. The research found that situational and individual factors influenced students' willingness to communicate in class. The majority of students willing to use English in class interactions was at a high level, and the following factors influenced such: Communication Behavior factor, Behavioral Intention, Situated Antecedents, Motivation Propensities, Affective-Cognitive context, and Social-individual context